2021
DOI: 10.3390/jcm10112528
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Patients with Prader-Willi Syndrome—A Systematic Review of Observational and Interventional Studies

Abstract: Physical activity (PA) is an important aspect of the management of patients with Prader-Willi syndrome (PWS). However, the day-to-day implementation of PA programs is particularly challenging in these patients. This systematic review aimed (1) to describe habitual PA and sedentary behavior and (2) to assess the effects of PA interventions and to describe their implementation process, in children and adults with PWS. A systematic search of controlled trials, single-group interventions, observational, and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(199 reference statements)
0
10
0
Order By: Relevance
“…This could be an important consideration for patients, perhaps giving the ability to eat regularly, rather than diet, or could work in conjunction with a low-fat, low-calorie diet regimen. Habitual physical activity levels are significantly lower in patients with PWS compared to both controls with and without obesity [57]. It was anticipated that, like N2KO mice treated with CLA [14][15][16], PWS mice would demonstrate increased 24 h spontaneous wheel running with CLA treatment compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an important consideration for patients, perhaps giving the ability to eat regularly, rather than diet, or could work in conjunction with a low-fat, low-calorie diet regimen. Habitual physical activity levels are significantly lower in patients with PWS compared to both controls with and without obesity [57]. It was anticipated that, like N2KO mice treated with CLA [14][15][16], PWS mice would demonstrate increased 24 h spontaneous wheel running with CLA treatment compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Besides obesity, PWS patients have lower muscles mass compared to obese subjects with similar characteristics but without PWS 6 , 7 . This leads to a significant reduction of energy expenditure in individuals with PWS due to low resting energy expenditure but also from reduced physical activity 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no adverse events have been found following physical activity programs in patients with PWS, although continuous supervision and support from experienced personnel is required. Very recently, a systematic review of controlled trials including 25 studies evaluated the effectiveness of physical activity interventions in patients with PWS and confirmed that both total volume of physical activity and physical exercise-related energy expenditure were lower in patients with PWS compared to patients with non-syndromic obesity [50]. Although no significant effect on weight and FM in children with PWS was observed, habitual physical activity programs were positively associated with lean body mass and bone parameters, and with improved physical function, not only in terms of muscle strength and walking distance, but also as locomotors coordination.…”
Section: Etiological Mechanisms Of Weight Gain In Patients With Pwsmentioning
confidence: 96%
“…Physical activity plays a pivotal role in the energy balance in patients with PWS [50]. Several studies indicate that both children and adults with PWS perform less physical activity than age-matched controls without PWS [51,52].…”
Section: Etiological Mechanisms Of Weight Gain In Patients With Pwsmentioning
confidence: 99%